Políticas Públicas alimentares em Fortaleza: histórico, legislação e distribuição espacial (2005-2023) - Bezerra, Maiara Colares (2024)
The objective of this work was to analyze which Public Food Policies were implemented in the city of Fortaleza from its Municipal Plan for Food and Nutritional Security, aiming to carry out a discussion about the Spatial Distribution of these Food Policies in the capital of Ceará, evaluating whether these actions have reached the most vulnerable population of the city. For this, it was initially necessary to carry out a discussion on the theme of Public Policies in order to support the analysis posed, then a historical survey was carried out on the legislation and policies of FNS that were emerging in Brazil and Ceará, and the influence that these laws and policies inserted at the federal and state levels exerted on the city of Fortaleza. To support the research, it was also necessary to understand the term Social Vulnerability and the indicators used to calculate this vulnerability, in order to check the data of which neighborhoods in the city of Fortaleza had the highest numbers of vulnerability. With this, and after reaching both data, those referring to the Public Food Policies that were implemented in the city of Fortaleza and which were the neighborhoods of Fortaleza that had the highest rates of vulnerability, a parallel was made between the information and we arrived at the final results of this research. The time frame of the research (2005-2023) was defined as marking the beginning of discussions on Public Food Policies in Fortaleza. However, the text makes references to previous years to contextualize information. The methodology used included a literature review and interviews with representatives of Consea Fortaleza (Council for Food and Nutritional Security of Fortaleza) and Cosan Fortaleza (Coordination of Integrated Management of Food and Nutritional Security of Fortaleza). The results obtained show that, although the municipality's Public Food Policies have reached some points of social vulnerability in Fortaleza, there are still significant flaws in the distribution of these policies among the most vulnerable neighborhoods. Many of these neighborhoods with high IVS (Social Vulnerability Index) remain in an apparent state of public abandonment in relation to municipal food policies.